Evasão fiscal em micro e pequenas empresas: reflexões sobre o comportamento empreendedor - Belo, Marina Emanuelli (2019)
In running his business, the entrepreneur assumes the risks and responsibilities inherent in organizational activities and often faces internal conflicts associated with maximizing income to the detriment of rule breaking. In this sense, to circumvent adverse situations in the business environment, including evading bureaucracy and circumventing supervision, the entrepreneur may use a social mechanism called Brazilian “jeitinho”, which involves breaking rules and, although presenting distinctions, is often associated to corrupt acts. The set of attitudes intentionally performed by members of the organization that result in violation of social norms and standards is called organizational misbehavior, and among the illicit activities performed privately, tax evasion appears to be the most relevant practice in micro and small enterprises. Thus, considering that organizational behavior, including deviant attitudes such as misbehavior, is directly associated with the entrepreneur's individual conduct, this paper aims to understand how entrepreneur’s misbehavior is associated with tax evasion practices in micro and small businesses. companies. To conduct the research, an exploratory-descriptive study with a qualitative approach was performed, in which data collection occurred from semi-structured interviews conducted in two phases, first selected by convenience accountants who provide services to micro and small companies and, later, , intentionally chosen, entrepreneurs who act as owners in companies of this size. The results, obtained from the content analysis of the interviews, indicate that tax evasion is a common practice among entrepreneurs and is usually justified by a sum of factors, such as: low perception of the return of taxes collected by management public perception, perception of impunity and low supervision by the control agencies and the search for maximization of income, mainly as a way of business survival. The analysis of the data shows that tax evasion is associated with the misbehavior of the entrepreneur who intentionally uses tax evasion as a “way” to obtain the desired results to circumvent the adverse situations that prevent his company from maintaining or growing.